2022
DOI: 10.1002/open.202200171
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Microreactor Concept for the Continuous Kolbe Electrolysis of Carboxylic Acids Using Aqueous Electrolyte

Abstract: The Kolbe electrolysis is a promising reaction to combine the usage of electrons as reagents and the application of renewable generated carboxylic acids as raw materials producing value added chemicals. Within this study, the electrolysis was conducted in a specially developed concept electrochemical microreactor and draws the particular attention to continuous operation and reuse of the aqueous electrolyte as well as of the dissolved unreacted feedstock. The electrolysis was conducted in alkaline aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…[27] Also Baumgarten et al observed a negative impact while re-saturating carboxylate during a Kolbe electrolysis. [14] Adding neutralized (via addition of KOH) carboxylate instead of the acid itself, however leads to a further increased carbonate concentration with every resaturation -enhancing negative effects on the Kolbe electrolysis. This problem is avoided by re-dosing the acid itself.…”
Section: Continuous Operation Using Excess Valeric Acidmentioning
confidence: 99%
See 4 more Smart Citations
“…[27] Also Baumgarten et al observed a negative impact while re-saturating carboxylate during a Kolbe electrolysis. [14] Adding neutralized (via addition of KOH) carboxylate instead of the acid itself, however leads to a further increased carbonate concentration with every resaturation -enhancing negative effects on the Kolbe electrolysis. This problem is avoided by re-dosing the acid itself.…”
Section: Continuous Operation Using Excess Valeric Acidmentioning
confidence: 99%
“…Thus, the products of electrochemical transformations (e. g., hydrogenations, hydrodeoxygenations, decarboxylations) of polar biogenic compounds are often significantly less polar than their precursors, leading to a reduced solubility and therefore the option to achieve a separation of the insoluble product phase (liquid or solid) from the electrolyte phase. [8,[12][13][14] Kolbe reactions are generally performed at slightly acidic pH values. [15] This pH range can be understood as a compromise between the necessary acidic reaction conditions to avoid the Hofer-Moest-reaction [16] (see Scheme 1) on the one hand and the required deprotonation of the carboxylic group for a sufficiently high carboxylate concentration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations